Structure and physical stability of hybrid model systems containing pork meat and superworm (Zophobas morio larvae): The influence of heating regime and insect: meat ratio. (October 2020) - Scholliers, Jana; Steen, Liselot; Fraeye, Ilse
Abstract: Hybrid model systems, containing pork shoulder meat and Zophobas morio larvae in different insect:meat ratios, were subjected to isothermal heating at 70 or 80 °C to investigate how this would affect the rheological behavior, water holding properties and textural properties of these model systems. Meat and insect model systems were also studied for comparison. Rheological and textural characteristics were significantly higher in meat model systems compared to insect and hybrid model systems. Furthermore, insect:meat ratio had little to no effect on the studied attributes of the hybrid model systems. It was also demonstrated that heating the hybrid model systems at 80 °C resulted in similar viscoelastic and water holding properties compared to meat model systems heated at 70 °C. However, even when heated at this higher temperature, the maximum force measured during penetration of the hybrid model systems was still approximately 3 times lower compared to meat model systems. Industrial relevance: This study investigated the effect of insect:meat ratio and heating temperature on structure formation and water holding in hybrid model systems. The results offer important insights with regard to the composition and processing of hybrid meat products. They indicate that similar viscoelastic and water holding properties compared to meat products may be obtained by applying higher heating temperatures. However, results showed that obtaining the desired texture may pose an important challenge when developing hybrid meat products. Highlights: Structure formation and water holding in hybrid model systems was studied. Overall, meat model systems showed better properties than hybrid model systems. Insect:meat ratio had little to no effect on the properties of hybrid model systems. Hybrid model systems had good viscoelastic and water holding properties at 80 °C. Hybrid and insect model systems had poor textural properties at 70 and 80 °C.